Sintesis Nanopartikel Perak Menggunakan Ekstrak Daun Salam (Syzygium polyanthum) Sebagai Bioreduktor Dan Uji Aktivitasnya Sebagai Antioksidan - Taba, Paulina; Parmitha, Nadya Yuli; Kasim, Syahruddin (Indonesian Journal of Chemical Research, 2019)
Silver nanoparticles have been synthesized by the reduction method using salam leaf extract (Syzygium polyanthum) as a reducing agent. The silver nanoparticles produced were then tested for their activity as antioxidants. The formation of silver nanoparticles was carried out by adding the leaf extract into the solution of AgNO3 and homogenized using a magnetic stirrer. A UV-Vis spectrophotometer was used to confirm the formation of silver nanoparticles. Particle Size Analyzer (PSA), Scanning Electron Microscope (SEM), X-Ray Diffractometer (XRD) and Fourir Transform Infra Red (FTIR) spectrometers were used to characterize the nanoparticles produced before being tested for antioxidant activity. The results showed that the absorbance value increased with increasing reaction contact time. The maximum uptake was obtained at wavelengths of 432-446 nm using a UV-Vis spectrophotometer. The particle size was determined using a PSA with an average particle size distribution of 45.7 nm. The average diameter of silver nanoparticles was 10.06 – 13.97 nm and the silver nanoparticles had rod-shapes. Functional groups that play a role in the synthesis of nanoparticles were –OH, –C=O, and –C-O groups. Silver nanoparticles inhibited free radicals as antioxidants with the IC50 value of 582.7 ppm.